Enhancing STEM engagement and confidence: The impact of the Verizon Innovative Learning STEM Achievers Program on middle school students’ attitudes and perceptions - Maiden, James; Stewart, Delarious O.; Holloway, Kali (American Journal of STEM Education, 2025)
The Verizon Innovative Learning STEM Achievers Program increases middle school students’ interest, motivation, and confidence in STEM, focusing on underrepresented communities. Incorporating hands-on learning, mentorship, and emerging technologies like augmented reality, 3D design, and robotics, the program fosters early exposure to STEM disciplines. This study analyzes pre- and post-survey data from 121 participants using paired t-tests to measure changes in interest and attitudes. Results show significant improvements in enjoyment of STEM concepts, motivation in STEM classes, and confidence in STEM abilities. The findings underscore the importance of early STEM exposure, mentorship, and belonging in engaging underrepresented populations, contributing to efforts to reduce disparities and promote long-term interest in STEM fields.